2021
DOI: 10.1111/sdi.13033
|View full text |Cite
|
Sign up to set email alerts
|

Does the interference phenomenon affect strength development during same‐session combined rehabilitation program in hemodialysis patients?

Abstract: Introduction: This study aimed to assess if an interference effect could blunt the neuromuscular gains induced by a same-session combined rehabilitation in hemodialysis (HD) patients.Methods: Patients exercised twice a week, for 16 weeks, over their HD sessions.They were either always trained with resistance and endurance exercises (continuous training, "CONT") or alternatively with 1 week of resistance alternated with 1 week of endurance (discontinuous training, "DISC"). Adherence and workload were continuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…Similarly, after 12 weeks, an intradialytic aerobic exercise program ameliorated frailty, as reflected by the Fried frailty score ( P < .001), gait speed ( P < .001), physical activity ( P < .001), exhaustion ( P = .002) and SPPB score ( P = .002) [ 39 ]. Recently, we showed that pre-dialytic exercise training improved the SPBB score and one-leg balance [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, after 12 weeks, an intradialytic aerobic exercise program ameliorated frailty, as reflected by the Fried frailty score ( P < .001), gait speed ( P < .001), physical activity ( P < .001), exhaustion ( P = .002) and SPPB score ( P = .002) [ 39 ]. Recently, we showed that pre-dialytic exercise training improved the SPBB score and one-leg balance [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The training effect of the experiment was tested by isokinetic muscle strength test and the center height after difficult take-off. 4,5 The experimental period was from November 2010 to January 2011, and the experimental period was three months. Upon application, the martial arts center agrees to assist the coaches of the women's martial arts team to carry out lower limb strength training for three months, twice a week for 13 weeks.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Recent works reported the feasibility of moderate load eccentric bed cycling during dialysis and the use of eccentric‐overload resistance exercise as a potential treatment to combat decline in physical function in people with chronic kidney disease (CKD; Pavlin et al, 2022). (Gollie et al, 2020).…”
Section: Introductionmentioning
confidence: 99%